Evaluation of potential ornamental plants in Sg. Rawog conservation area, Sandakan, Sabah and it’s conservation status - Jesleen Linus Dani; Andy Russel Mojiol; Nurliza Hasmat; Colin Goh; Paul Liau (e-VIBS, Faculty of Science and Natural Resources, 2023)
Wild flora with high attractiveness and has been long prized for its beauty will be planted in gardens and other recreational places to enhance the landscape beautification. Foliage arrangement, branching pattern, and the presence of fruit and flower provide interest, variety and aesthetic appeal to landscapes and even to observers. This study was carried out in Sg. Rawog Conservation Area (SRCA) within the KTS Plantation vicinity. The main objective of this study was to identify ornamental plants, and their International Union Conservation of Nature (IUCN) categories based on conservation status and endemism by using the opportunistic sampling method. The selection of the ornamental plant is based on five criterions: 1) It has a good form, shape and size of the plant, 2) It has colorful flowers and fruits, 3) It has attractive colors and arrangement of the foliage, 4) it has good branching pattern, and 5) it is easy for plant to propagate. The survey was conducted twice, in June and August 2019, in existing trails. A total of 24 species belong to 17 different families. The highest number of potential ornamental plants found in Sg Rawog Conservation Area is the Tree (29.2%) followed by the Fern (16.7%) and Shrub (20.8%), Herb (12.5%), 8.3% of which are shared by two plants habit (Pitcher and Palm), and lastly, the lowest is Climber (4.2%). Most plants are in the category Not Evaluated based on IUCN Red List except Dryobalanops aromatic, Dicranopteris linearis, Nepenthes ampularia, and Nepenthes mirabilis. The findings of this study indicate that Sg. Rawog Conservation Area is a home to a large number of plants with the potential of to become ornamental plants, and it plays an essential role in the protection of these species in Sabah. More research may be required to expand the list of plants with the potential to become ornamental plants.